Acetabular reconstruction with an ice‐cream cone prosthesis following resection of pelvic tumors: Does computer navigation improve surgical outcome?. Issue 7 (9th March 2020) - Fujiwara, Tomohiro; Sree, Deepak V.; Stevenson, Jonathan; Kaneuchi, Yoichi; Parry, Michael; Tsuda, Yusuke; Le Nail, Louis‐Romée; Medellin, Ricardo M.; Grimer, Robert; Jeys, Lee
Abstract: Background and Objectives: Acetabular reconstruction with a coned‐stem prosthesis has been one of the reliable procedures following pelvic tumor resections but is associated with a risk of complications and postoperative morbidity. We investigated whether navigated reconstruction could decrease the complication rate and optimize outcomes. Methods: A retrospective study was conducted on 33 patients who underwent acetabular resection and reconstruction with ice‐cream cone prostheses; outcomes were compared between the navigated and nonnavigated groups. Results: A clear margin was obtained in 91% and 82% of the navigated and nonnavigated groups, respectively. The local recurrence (LR) rate was 12%, and all LRs occurred in the nonnavigated group. The rate of major complications requiring surgical intervention was significantly lower in the navigated group (9%) than in the nonnavigated group (50%; P  = .024). Two implant failures occurred in the nonnavigated group. Functional outcomes were significantly correlated with the occurrence of major complications ( P  = .010) and the use of navigation ( P  = .043); superior functional scores were observed in the navigated group (Musculoskeletal Tumor Society, 73% vs 55%; Toronto Extremity Salvage Score, 73% vs 56%). Conclusion: Ice‐cream cone prosthesis is an acceptable reconstruction modality following periacetabular tumor resections, and computer navigation are useful to facilitate proper resection margins and implant position.